2011
DOI: 10.1111/j.1600-0897.2011.01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐HY Responses in Pregnancy Disorders

Abstract: Problem Cellular and humoral immune responses against male-specific minor histocompatibility (HY) antigens are important in the pathogenesis of graft-versus-host reactions and can be detected in women who have previously given birth to a boy. However, the importance of these responses for pregnancy outcome is unclear. Method of study Review of the current knowledge about the impact of anti-HY immunity on pregnancy outcome in terms of risk of miscarriage, placental abrup-tion and low birth weight. Results Women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Specifically, Christiansen et al have found that women who experience secondary recurrent miscarriage are more likely than the general population to possess the appropriate Class II MHC to present Y‐chromosome‐encoded mHAgs and that secondary recurrent miscarriage is more likely to occur in women who have previously given birth to a male baby, thus presenting the possibility that the development of secondary recurrent miscarriage is related to the generation of a maternal immune response specific for Y‐chromosome‐encoded antigens during the preceding, successful pregnancy. One theory regarding this phenomenon is that pregnancy complications late in the first pregnancy may disrupt the tolerogenic environment required for maintaining maternal immune tolerance toward the fetus and that this disruption contributes to the failure of subsequent pregnancies, especially those with a male fetus . It is important to note that disruption of the tolerogenic environment and maternal T‐cell recognition of both autosomal and Y‐chromosome encoded fetal mHAgs may contribute to many cases of idiopathic infertility as well as numerous pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Christiansen et al have found that women who experience secondary recurrent miscarriage are more likely than the general population to possess the appropriate Class II MHC to present Y‐chromosome‐encoded mHAgs and that secondary recurrent miscarriage is more likely to occur in women who have previously given birth to a male baby, thus presenting the possibility that the development of secondary recurrent miscarriage is related to the generation of a maternal immune response specific for Y‐chromosome‐encoded antigens during the preceding, successful pregnancy. One theory regarding this phenomenon is that pregnancy complications late in the first pregnancy may disrupt the tolerogenic environment required for maintaining maternal immune tolerance toward the fetus and that this disruption contributes to the failure of subsequent pregnancies, especially those with a male fetus . It is important to note that disruption of the tolerogenic environment and maternal T‐cell recognition of both autosomal and Y‐chromosome encoded fetal mHAgs may contribute to many cases of idiopathic infertility as well as numerous pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%
“…The trophoblast cells that invade the endometrium, specifically extravillous cytotrophoblast, come into direct contact with T cells, but they are inhibited by factors secreted from both the trophoblast and decidualised endometrium, such as indoleamine 2,3-dioxygenase and soluble HLA-G, implying their functions can be dangerous to the developing conceptus19. Despite the release of these factors, inhibition is not complete and T cell responses directed towards the conceptus are formed; peripheral and decidual T cells restricted by male-specific minor histocompatibility (HY) antigens can be detected throughout pregnancy and postpartum202122 and T cells may be activated by other factors such as NK cell receptor ligands23. There is evidence that an immunological memory response to pregnancy can be generated as secondary RM is more frequent after a first successful male, rather than female pregnancy24; and pregnancies ending in miscarriage rather than live birth are associated with an increased risk of further miscarriage25.…”
mentioning
confidence: 99%
“…The neonatal conditions linked to alloimmunization include fetal and neonatal alloimmune thrombocytopenia [126,127], fetal and neonatal hemolytic anemia [128], alloimmune neonatal neutropenia [129], hydrops fetalis [130], neonatal hemochromatosis [131], biliary atresia [132], and neonatal glomerulopathy [133]. Alloimmunization was also proposed to at least partially explain implantation failure, recurrent pregnancy loss and pre-eclampsia/eclampsia [134,135] as well as inflammatory lesions of the placental villi during pregnancy [136]. It is therefore clear that the lessons learned from genetics of lupus and autoimmunity in general may have a broader impact than initially thought.…”
Section: Discussionmentioning
confidence: 99%